GamR, the LysR-Type Galactose Metabolism Regulator, Regulates hrp Gene Expression via Transcriptional Activation of Two Key hrp Regulators, HrpG and HrpX, in Xanthomonas oryzae pv. oryzae - Rashid, M. Mamunur (Appl Environ Microbiol, 2016)
Xanthomonas oryzae pv. oryzae is the causal agent of bacterial leaf blight of rice. For the virulence of the bacterium, the hrp genes, encoding components of the type III secretion system, are indispensable. The expression of hrp genes is regulated by two key hrp regulators, HrpG and HrpX: HrpG regulates hrpX, and HrpX regulates other hrp genes. Several other regulators have been shown to be involved in the regulation of hrp genes. Here, we found that a LysR-type transcriptional regulator that we named GamR, encoded by XOO_2767 of X. oryzae pv. oryzae strain MAFF311018, positively regulated the transcription of both hrpG and hrpX, which are adjacent to each other but have opposite orientations, with an intergenic upstream region in common. In a gel electrophoresis mobility shift assay, GamR bound directly to the middle of the upstream region common to hrpG and hrpX. The loss of either GamR or its binding sites decreased hrpG and hrpX expression. Also, GamR bound to the upstream region of either a galactose metabolism-related gene (XOO_2768) or a galactose metabolism-related operon (XOO_2768 to XOO_2771) located next to gamR itself and positively regulated the genes. The deletion of the regulator gene resulted in less bacterial growth in a synthetic medium with galactose as a sole sugar source. Interestingly, induction of the galactose metabolism-related gene was dependent on galactose, while that of the hrp regulator genes was galactose independent. Our results indicate that the LysR-type transcriptional regulator that regulates the galactose metabolism-related gene(s) also acts in positive regulation of two key hrp regulators and the following hrp genes in X. oryzae pv. oryzae. IMPORTANCE The expression of hrp genes encoding components of the type III secretion system is essential for the virulence of many plant-pathogenic bacteria, including Xanthomonas oryzae pv. oryzae. It is specifically induced during infection. Research has revealed that in this bacterium, hrp gene expression is controlled by two key hrp regulators, HrpG and HrpX, along with several other regulators in the complex regulatory network, but the details remain unclear. Here, we found that a novel LysR-type transcriptional activator, named GamR, functions as an hrp regulator by directly activating the transcription of both hrpG and hrpX. Interestingly, GamR also regulates a galactose metabolism-related gene (or operon) in a galactose-dependent manner, while the regulation of hrpG and hrpX is independent of the sugar. Our finding of a novel hrp regulator that directly and simultaneously regulates two key hrp regulators provides new insights into an important and complex regulation system of X. oryzae pv. oryzae hrp genes.